# 45-[4-2y-4(y+7)]= -4(1+3y)-[4-3(y+2)-2(2y-5... solve for y?

Question:16 People have tried to help me work this problem. All of the problems like it in the book come out to be a whole # . I think this problem should come out to be a wole number Everytime I do it I get a fraction. Anyone get a whole number?

Let's see if I can do this by eyeballin' it. Focus on just the left side of the equation.

First, every time you see something like 4(3-y), multiply it out: 12-4y. (Do it, whatever it's called.)

Next, simplify each side of the equation by adding up the constants and the variables.

First, left side constants: 45-(4-28)= 45 - (-24) = 69.
Variables: - (-2y-4y) = - (-6y) = 6y.
Left side is 6y+69.

Right side constants: -4-[(4-6-10)] = -4 - (-12) = -4 + 12 = 8.
And: -12y-[(-3y-4y)] = -12y - (-7y) = -12y + 7y = -5y.
So, the right side is 5y + 8.

So the equation reduces to : 6y + 69 = -5y - 8
Git all the constants on one side, and variables on t'other, by addition or subtraction:
add 5y both sides: 11y + 69 = -8
subtract 69 from both sides: 11y = -8-69 = -77
divide both sides by 11: y = -77/11 = -7

Try again: Left side
45-4+2y+4y+28 = 6y + 69

Right side
-4-12y-4+3y+6+4y-10 = -5y -12

6y + 69 = -5y -12
11y + 69 = -12
11y = -81
y = -81/11 = -7 4/11

That seems to work.

The hardest thing is making sure that every 'negative' sign applies to exactly each term that it's meant to...no more, no less. Only suggestions: First, when you think you have an answer, plug it into the equation to see if the two sides are equal. If they aren't, that wasn't the answer.

Second, don't apply too many 'negatives' at once. (that confuses me, too) for example: Simplify everything in the brackets [ ] on the right side of the equation, and THEN apply the 'negative' in front of it.

Hope this helps.

Ciao.
I do not have a whole number. If you posted the whole equation and I calculated it correctly, my answer would be
-8 1/11 or -89/11.

It took a really long time to compute.
y equals 12
Take one side of the equation at a time...do your multiplication first ...[-4xy+-4x7]...then combine your like terms. Do teh same procedure for teh other side of the equation. (you should get 13 - 6y=-4 - 19y) then add (19y) to both sides of the equation then subtract (13) from both sides and you will get a negative improper fraction.

This article contents is post by this website user, EduQnA.com doesn't promise its accuracy.